Pain Awareness and Medication Knowledge: A Health Literacy Evaluation. (27th February 2013) - Devraj, Radhika; Herndon, Christopher M.; Griffin, Jake
ABSTRACT Chronic pain is a significant burden to the US health care system. Patient-related barriers such as low health literacy can prevent optimal management of pain. This study aimed to determine the relationship between health literacy, pain awareness, and medication knowledge. Chronic pain patients visiting a family health center were administered a survey addressing the study objectives. Health literacy was measured using the Newest Vital Sign. A total of 139 chronic pain patients participated in the study. Patients with low health literacy had significantly lower overall pain medication knowledge (mean score = 63.3± 18.9 versus 74.3 ± 18.5, p <0.05), and did not know where to find health care professionals to help manage their pain. Patients with low health literacy lacked knowledge of non-medication modes of treating pain, and did not know which non-prescription medications could provide pain relief. The mean Visual Analogue Scale score for the entire sample was 51.54 mm (range = 0 − 100 mm). Pain intensity was not related to health literacy (p > 0.05). Multivariate analyses showed a significant relationship between health literacy and medication knowledge after controlling for demographics. Patients with low health literacy have poor knowledge of pain medications. Educational interventions to meet the needs of patients with low health literacy are essential to safely relieve pain.